THE EFFECTIVENESS OF IMPLEMENTING A CARING BUREAUCRACY BY NURSE MANAGERS IN REDUCING BURNOUT LEVELS - Hayati, Dewi; Mustaqimah; Firmansyah, Hendra; manggarsari; Hayati, Nur; Jamaludin, Mohtar; Sihwastuti (Rifapublisher.id, 2024)
Background: As the majority in health organizations, nurses can impact the quality of health care as a whole. Nurse burnout are clinical syndrome of physiology and psychology that can manifest as mental, physical, and emotional exhaustion. This syndrome was caused by front line nurse workforce. Nurse managers as a part of the organizational structure had the responsibility to apply bureaucratic enpowerment to achieve quality nursing care. Application of bureaucratic caring can lowered nurse’s burnout with interpersonal and structural relations to increase nurse’s motivation. Objective: The purpose of this research is to analyze the effectivity of the bureaucratic caring application of nurse managers toward nurse practitioners in building A RSCM. Method: This research used experiment and single blind with 42 respondents. Data gathering process using random sampling. The results of this study found that there was a difference in the average burnout rate in implementing nurses before and after the implementation of caring bureaucracy for nurse managers in the control group. In the intervention group, there was no difference in the average burnout rate among nurses. Conclusion: Caring nurse managers can’t affect the burnout rate of implementing nurses.